The historiographic field of Japanese immigration: some outlines: O campo historiográfico da imigração japonesa: alguns delineamentos (Revista de História da UEG (REVHIST), 2021)
The aims of this paper is to analyze the historiographic field of Japanese immigration, understood as an area formed by several authorities who search comprehension of the immigration process through concepts, like: acculturation, assimilation, negotiates identity, and japonesidades. Therefore, we understand this field is subdivided in three phases: the first is called acculturation and assimilation due the researches using mainly these two joint concepts to integration and accommodation. This phase arose and was consolidated in the 1930s and 1940s, having as great authority Hiroshi Saito; the second emerged about the years 2000, and is called ethnicity, because the studies withdraw of concept of assimilation, and focus more in the ethnicity and the issue of identity, that way, the great authority is the brazilianist Jeffrey Lesser, the inaugurator this phase, and was establish the concepts of negotiation, and identity hyphenated and situational. Lastly, we suggest that there is a delineation of a third phase that seeks to break up, or at least put away, the concepts from the previous phase, since they are comprehended as inadequate for understanding the immigration phenomenon, and subjective construction of Nikkei’s.Keywords: historiographic field. Japanese immigration. Assimilation. Acculturation. Identity negotiated. Japonesidades.